Management of Incidental Hernia Discovered During Abdominal Contouring in Post–Bariatric Surgery Patients. Issue 5 (November 2018) - Levy, Adam S.; Dinesh, Anant; Ahmed, Leaque; Morrison, Norman; Engdahl, Ryan
Abstract : Purpose: An increase in bariatric surgery has led to a rise in postbariatric contouring procedures. Despite a comprehensive preoperative assessment, body habitus in these patients may significantly limit the abdominal exam. Abdominal contouring procedures typically elevate large portions of the skin and fat off the abdominal wall, and unexpected hernia may be discovered intraoperatively. No study to date has characterized such hernia discovery at the time of body contouring surgery. We reviewed our experience of management of incidental hernia found during abdominoplasty or panniculectomy after laparoscopic bariatric surgery. Methods: Records of all post–bariatric surgery patients undergoing abdominal contouring procedures between 2007 and 2017 were reviewed to identify patients with incidental hernias discovered intraoperatively. These patients were further examined by reviewing operative details, patient-specific factors, and outcomes. Results: Six hundred eighty-one post–bariatric surgery patients underwent abdominal body contouring procedures with incidental ventral hernia discovered in 36 patients (5.3% [45 hernias]). At the time of plastic surgery, average age was 49 years (range, 25–64 years), and body mass index was 30.7 kg/m 2 (range 25–43 kg/m 2 ). Of 36 patients with incidental hernia, 26 patients (72.2%) had a single hernia, and the remainder had multiple (27.8%). Mean hernia size was 4.1 cm 2 (range, 0.25–24 cm 2 ). Most hernias were located paraumbilical/umbilical (46.7%) or epigastric (37.8%). Ninety-eight percent of hernias were repaired primarily (n = 44) by the plastic surgeon, and in 1 case (2%), mesh repair was performed by a consulting general surgeon. Average follow-up was 1.9 ± 0.3 years. Only 1 patient (2.8%) developed hernia recurrence after 48 months. Other postoperative complications included superficial wound healing problems (19.4%), seroma (16.7%), suture abscess (5.6%), and cellulitis that resolved with antibiotics (5.6%). Conclusions: This is the first study to characterize incidental hernia discovered at the time of body contouring in the post–bariatric surgery patient. The body contouring surgeon should be aware of this common finding. Hernias typically discovered during panniculectomy or abdominoplasty arise in umbilical or epigastric regions, likely from prior laparoscopic port sites, and can be safely repaired by the plastic surgeon with low overall complication rates.